The Innovation of Minang Kayo Leather Handicraft Products as an Icon of Padangpanjang City - Asmidar, Asmidar; Saputra, Andra; Syafitri, Aini Ramadhani; Heruningrum, Heruningrum (Gorga : Jurnal Seni Rupa, 2025)
This research aims to identify and explore the product innovations of the Minang Kayo leather handicraft that have become an icon of Padangpanjang City. The Minang Kayo leather handicraft business is one of the leather craft businesses in Padangpanjang City. This business has become an icon of leather craftsmanship in the city and has contributed to the economy and tourism. Over time, this business has implemented various innovations in the products it creates. To address the issues in this research, a qualitative research method with an Innovation approach was used, employing data collection methods such as literature studies, observations, interviews, product documentation, and data analysis. Based on field findings, it can be concluded that the Minang Kayo leather handicrafts  in Padangpanjang City have a diverse range of innovative leather products, including shoes, wallets, bags, hats, belts, jackets, and highly creative and innovative leather sandals.